2008
DOI: 10.1144/jm.27.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary benthonic foraminifera in a bathyal core from the Leeward Islands, Lesser Antilles, NE Caribbean Sea

Abstract: The 3.13 m long bathyal piston core En20-2 from the northern Leeward Islands (17(49.9#N, 63(02.4#W, water depth 680 m) was sampled every 20 cm. The Pleistocene-Holocene boundary occurred at 107 cm, and the base of the core lay above the Atlantic extinction of Pulleniatina obliquiloculata (34 ka BP). The core yielded throughout both (a) a deep-water association (DWA) of middle bathyal benthonic foraminifera and (b) a shallow-water association (SWA; up to 56% of total recovery) comprising back-reef, epiphytal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…They found only subtle faunal changes at glacial-interglacial boundaries as defined using menardiform planktonic foraminifera, and noted that neither S nor H showed clear stratigraphic trends. Wilson (2008aWilson ( , 2011 did not find an abrupt community-level regime shift in benthonic foraminifera at the PleistoceneHolocene boundary (Termination I of Broecker & van Donk, 1970) in piston cores En20-2 and En20-10, taken from middle-bathyal depths in the eastern Caribbean Sea. He did, however, note that Trifarina bradyi Cushman and Hoeglundina elegans (d'Orbigny) were more abundant in the Holocene of En20-10, suggestive of species-level regime shifts.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They found only subtle faunal changes at glacial-interglacial boundaries as defined using menardiform planktonic foraminifera, and noted that neither S nor H showed clear stratigraphic trends. Wilson (2008aWilson ( , 2011 did not find an abrupt community-level regime shift in benthonic foraminifera at the PleistoceneHolocene boundary (Termination I of Broecker & van Donk, 1970) in piston cores En20-2 and En20-10, taken from middle-bathyal depths in the eastern Caribbean Sea. He did, however, note that Trifarina bradyi Cushman and Hoeglundina elegans (d'Orbigny) were more abundant in the Holocene of En20-10, suggestive of species-level regime shifts.…”
Section: Introductionmentioning
confidence: 91%
“…Abrupt regime shifts have been inferred in bathyal (200-2000-m depth) and abyssal (.2000 m) foraminiferal community structures between glacials and interglacials in parts of the Atlantic Ocean and Gulf of Mexico (Streeter, 1973;Schnikter, 1974Schnikter, , 1980Streeter & Lavery, 1982;Denne & Sen Gupta, 2003) and in the eastern Caribbean Sea (Gaby & Sen Gupta, 1985;Sen Gupta et al, 1991;Wilson, 2008aWilson, , 2011. Although the strength of the shifts has rarely been quantified, it is apparent that, as in the ostracode and planktonic foraminiferal examples given above, this glacial-interglacial signal is not equally marked everywhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The succession of abundance biozones differed between the three cores, although taken only ~150 km apart and from similar water depths, indicating that the region is one of considerable oceanographic complexity. This is reflected in the distinct benthonic foraminiferal associations found in these cores (Wilson 2011), which, once again, do not show any marked glacial-interglacial contrasts (Wilson 2008) but show that the organic flux in the northeast Caribbean Sea decreased gradually through the Late Quaternary. Wilson (2013) recorded a major regime shift during MIS 8-9 in the Upper Quaternary of ODP Hole 1006A (Santaren Channel, offshore western Bahamas), but otherwise found only weak evidence of Milankovich cycles, Globocassidulina subglobosa (Brady, 1881) and Cibicidoides aff.…”
Section: Ontological Decisions and The Use Of Paleontological Data Fomentioning
confidence: 81%
“…However, they suggested Nuttallides umbonifera , Bulimina buchiana dOrbigny and Chilostomella oolina Schwager to be rarer in the last glacial than in the two bounding glacials. Wilson [22], [23] examined the benthonic foraminifera in two bathyal piston cores near the northern Leeward Islands, eastern Caribbean Sea. He did not find any marked faunal changes at the Pleistocene-Holocene boundary, but showed that the organic flux in one core decreased gradually through the entire core.…”
Section: Introductionmentioning
confidence: 99%